P08.12.B Conceptual development of an intensive supervised exercise program for brain tumor patients: summary of clinical experience. (5th September 2022) - Jost, J; Brandt, R; Altuner, U; Müther, M; Stummer, W; Völker, K; Wiewrodt, R; Wiewrodt, D
Abstract: Background: Several studies have identified beneficial effects of physical activity on reducing cancer-related symptoms. However, the number of such studies in neuro-oncology is limited, and even today, brain tumor patients are often advised against physically strenuous exercise. Here we summarize our experience with an individualized training program in brain tumor patients over a period of more than 8 years. Material and Methods: Patients with primary brain tumors were invited to participate in the individual training program as part of the psycho-oncological consultation. If interested and free of major comorbidity, a professional sport scientist/diploma coach individualized two 60-minute sessions/week adapted to the patients' respective symptoms and trained them on a 1:1-basis. One session consisted of bicycle ergometry at an average workload of 75% of the max. age-adjusted heart rate (up to 95% at peak; continuous monitoring throughout entire session), the other session was progressive whole-body resistance training based on 10 separate, but standardized exercise tasks using the university's training facilities. Both training sessions were complimented by challenging elements to improve coordination. Exercise tasks were adapted as needed, and exercise levels were enhanced over time, if possible. Results: From 2011 to 2019, 45 patients (19 women, 26 men) aged 20-76 years (mean 49) with different tumor types (65% high-grade gliomas, 22% low-grade gliomas, 13% other) participated in the program. The majority of patients started the program following concurrent radio-chemotherapy and in parallel with adjuvant systemic therapy. On average, 41 training sessions were performed. No training-related adverse events (e.g., falls, head pain, etc.) occurred during the entire period. In a total of 1828 training sessions, two minor epileptic seizures occurred (1 speech arrest; 1 simple focal seizure, left hand affected). Both patients were familiar with the respective type of seizure before entering the program and training could be continued immediately, with reduced intensity. Seizures did not reoccur during subsequent training sessions. Conclusion: This supervised intensive physical training program with submaximal exertion zones was feasible, safe, and highly rated by all participants. Based on these experiences and the reported well-being of the patients, we launched a prospective oligocentric study to objectify the improvements in physical performance and quality of life in patients with glioblastoma (ClinicalTrials.gov Identifier: NCT05015543).